Characterisation of organic compounds in leachates from Matang and Mambong Landfills, Kuching - Francisca, Matsin. (Universiti Malaysia Sarawak, (UNIMAS), 2006)
Leachate is a liquid containing decomposed wastes, bacteria and other materials that formed within a landfill site that is comprised of water and materials that are leached from the wastes. Leaehates samples were collected from Matang and Mambong landfill of Kuching Division. The samples were extracted using dichloromethane and analysed on gas chromatography/mass spectrometer (GC/MS). Several organic pollutants were identified in the acid extractable fractions, base/neutral extractable fractions from leachate samples and extracts from Soxhlet extraction. The acid extractable compounds detected in leachate include the alcohol, ether, carboxylic acid, ester groups and also hydrogenated compounds. While the base/neutral extractable fractions from leachate consists of compounds from phthalate and phenol groups and also compounds containing nitrogen, phosphorus and silica. The particulate materials from leachate consist of compounds from groups of phthalate, ethers, acids, esters and alcohols.